Islamic Perspectives on the Consumption of Boy’s Love (BL): A Spiritual Well-Being Analysis - Ifandi, Muhamad Nanda Fifin; Jauhari, Rosy Maria Ulfa (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The consumption of Boy’s Love (BL) has rapidly expanded across various Asian countries and has become increasingly prominent in Indonesia due to enhanced digital access and the pervasive influence of transnational popular culture. This development raises questions regarding the understanding of BL consumption within the framework of Islamic values, particularly in relation to the spiritual well-being of Muslim individuals. This study aims to analyze Islamic perspectives on BL consumption through the Spiritual Well-Being framework, which encompasses Religious Well-Being (RWB) and Existential Well-Being (EWB). A literature review with a descriptive qualitative approach was conducted on 80 articles published between 2020 and 2025, sourced from Google Scholar, Semantic Scholar, ScienceDirect, and ResearchGate. The analysis employed thematic techniques to identify the relationships among BL media consumption, user motives, Islamic moral values, and individual spiritual dynamics. Findings indicate that BL consumption has the potential to challenge RWB, as the depiction of same-sex relationships conflicts with Islamic law and may influence moral sensitivity as well as the clarity of an individual's relationship with God. In the EWB dimension, BL serves as a space for escapism, identity exploration, and emotional fulfillment; however, the resulting meanings often misalign with Islamic life orientation, leading to existential dissonance. The study underscores that spiritual well-being in Islam requires the prudent management of media consumption to maintain the moral balance and spiritual orientation of Muslim individuals.